Biomarkers and Immune Repertoire Metrics Identified by Peripheral Blood Transcriptomic Sequencing Reveal the Pathogenesis of COVID-19 - Liu, Yang; Wu, Yankang; Liu, Bing; Zhang, Youpeng; San, Dan; Chen, Yu; Zhou, Yu; Yu, Long; Zeng, Haihong; Zhou, Yun; Zhou, Fuxiang; Yang, Heng; et al. (Frontiers in Immunology, 2021)
The COVID-19 pandemic caused by SARS-CoV-2 infection is a global crisis, however, our current understanding of the host immune response to SARS-CoV-2 infection remains limited. Herein, we performed RNA sequencing using peripheral blood from acute and convalescent patients, and interrogated the dynamic changes of adaptive immune response to SARS-CoV-2 infection over time. Our results revealed numerous alterations in these cohorts in terms of gene expression profiles and the features of immune repertoire. Moreover, a machine learning method was developed and resulted in the identification of 5 independent biomarkers and a collection of biomarkers that could accurately differentiate and predict the development of COVID-19. Interestingly, the increased expression of one of these biomarkers, UCHL1, a molecule related to nervous system damage, was associated with the clustering of severe symptom. Importantly, analyses on immune repertoire metrics revealed the distinct kinetics of T cell and B cell response to SARS-CoV-2 infection, with B cell response plateaued in the acute phase and declined thereafter, whereas T cell response can be maintained for up to 6 months post infection onset and T cell clonality was positively correlated with the serum level of anti-SARS-CoV-2 IgG. Together, the significantly altered genes or biomarkers, as well as the abnormally high levels of B cell response in acute infection may contribute to the pathogenesis of COVID-19 through mediating inflammation and immune responses, whereas prolonged T cell response in the convalescents might help these patients in preventing reinfection. Thus, our findings could provide insight into the underlying molecular mechanism of host immune response to COVID-19 and facilitate the development of novel therapeutic strategies and effective vaccines.